PENGELOLAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN - Silvia Ocdelina; Meyzi Heriyanto; Lena Farida (Universitas Riau, 2018)
Management of Rural and Urban Land and Building Taxes: This study aims toknow management of rurar and urban land and building taxes of of Siak Regency in 2011-2015.Type of Research which is a qualitative approach. Qualitative data which is the result of interviewsand a list of research objects. The data obtained is then analyzed through organizing data,translated into units, compiled into patterns, choosing which data is important and which will bestudied, elaborating in the form of words and sentences and as long as making conclusions.Research informants were section, intensification, extensification and billing sections. The resultsof the study indicate that the PBB P2 which cannot be said maximal because there are stillintersecting, among others update database, inadequate Human Resources and facilities that havenot accommodated PBB P2.